2007
DOI: 10.1080/10810730701438690
|View full text |Cite
|
Sign up to set email alerts
|

Does Entertainment-Education Work With Latinos in the United States? Identification and the Effects of a Telenovela Breast Cancer Storyline

Abstract: This article examines the proposition that a popular form of entertainment, the telenovela, can educate Spanish-speaking viewers in the United States if accurate health information is presented in a dramatic, narrative format. Health professionals consulted on a breast cancer storyline in a Spanish-language telenovela, Ladrón de Corazones, and the impact on viewers' knowledge and behavioral intentions were assessed using three methods. First, an analysis of call attempts to 1-800-4-CANCER demonstrated a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
105
1
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(114 citation statements)
references
References 22 publications
4
105
1
4
Order By: Relevance
“…While fotonovelas and other health education materials are considered effective in improving health knowledge and desire to seek treatment (Hinojosa et al 2010;Valle et al 2006;Wilkin et al 2007), few studies have evaluated which elements of such interventions engage and appeal to their audiences (Hawkins et al 2008). Despite limited use in past research, Larkey and Hecht's (2010) CCNHP model specifies several testable cultural (i.e., culturally familiar characters, language, and plausible storylines) and psychological elements (i.e., audience engagement and identification with storyline and characters, audience transportation or evoked emotions and consequent discussion of the topic and changes in attitudes and behaviors) as influencing health behavior change.…”
Section: Theoretical Frameworkmentioning
confidence: 98%
“…While fotonovelas and other health education materials are considered effective in improving health knowledge and desire to seek treatment (Hinojosa et al 2010;Valle et al 2006;Wilkin et al 2007), few studies have evaluated which elements of such interventions engage and appeal to their audiences (Hawkins et al 2008). Despite limited use in past research, Larkey and Hecht's (2010) CCNHP model specifies several testable cultural (i.e., culturally familiar characters, language, and plausible storylines) and psychological elements (i.e., audience engagement and identification with storyline and characters, audience transportation or evoked emotions and consequent discussion of the topic and changes in attitudes and behaviors) as influencing health behavior change.…”
Section: Theoretical Frameworkmentioning
confidence: 98%
“…10 For example, Cohen 11 pointed to the importance of character identification in vicarious learning, and recent studies have shown that character identification can moderate EE effects. 12,13 An alternative to Cohen's explanation is that, rather than identifying with fictional characters, regular viewers form parasocial relationships with them. 14,15 Such relationships deepen the emotional impact of "interactions" with characters, and that may help to explain why stronger EE effects have been demonstrated among regular viewers of a show than among less frequent viewers.…”
Section: Possible Mechanisms Of Ee Effectsmentioning
confidence: 99%
“…Entertainment-education research has found that feeling similar to characters, or adopting characters' perspective while viewing, can increase self-efficacy and positively impact story-consistent attitude and behavioral intentions (Green, Brock, & Kaufman, 2004;Sood, 2002;Wilkin, Valente, Murphy, Cody, Huang, & Beck, 2007). The E-ELM (Slater & Rouner, 2002) posits that identification and transportation function similarly in narrative persuasion.…”
Section: Future Researchmentioning
confidence: 99%